If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x-3(2x+1)=3
We simplify the equation to the form, which is simple to understand
4x-3(2x+1)=3
Reorder the terms in parentheses
4x+(-6x-3)=3
Remove unnecessary parentheses
+4x-6x-3=+3
We move all terms containing x to the left and all other terms to the right.
+4x-6x=+3+3
We simplify left and right side of the equation.
-2x=+6
We divide both sides of the equation by -2 to get x.
x=-3
| 5/6x=20/3 | | 9*7-4*3+5= | | -6y-12=-33 | | -6y-13=-33 | | x^2-32x+135=0 | | -5b-6-10b-8= | | 0.06x=100 | | 12.4=n+2.8 | | 8[4(n-4)+18]-[3(2n-3)+3]= | | 13n+13= | | 13+13= | | 6+.10=.15+8 | | (24y^7)/(12y^3) | | (17-2*3)-15= | | 9v=5v+8 | | 4(X+7)=5(X+6) | | 2x+6=3x+3 | | 5(w+2)=w+6(w-3) | | 8y+2=3y-13 | | (15-5*2)-17= | | -56=-7(-2+n) | | 1/2(n-8)=26 | | 74m=100 | | 59=-3b+5 | | -63m+257=.74 | | -63m+257=100 | | 6/x+7/y | | (-3x+12)/4 | | 2(4p+10)=26 | | -63m+257=74m | | x(x+4)=x^2-12 | | 102=6s+12 |